2004
DOI: 10.1016/j.febslet.2004.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Aβ aggregation in the presence of GM1‐ganglioside‐accumulated synaptosomes of aged apoE4‐knock‐in mouse brain

Abstract: Aging and apolipoprotein E4 (apoE4) expression are strong risk factors for the development of Alzheimer's disease (AD); however, their pathological roles remain to be clarified. In the process of AD development, the conversion of the nontoxic amyloid -protein (A) monomer to its toxic aggregates is a fundamental process. We previously hypothesized that A aggregation is accelerated through the generation of GM1 ganglioside (GM1)-bound A which acts as a seed for A fibril formation. Here we report that GM1 level i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 40 publications
5
76
0
Order By: Relevance
“…In this case, they suggested that aging and apoE4 expression cooperatively accelerated Ab aggregation in the brain through an increase in the level of GM1 in particular microdomains of neuronal membranes. These results suggest that Ab accumulation in these microdomains is an early event in the process of AD development (42).…”
Section: App Processing and Lipid Raftsmentioning
confidence: 63%
See 3 more Smart Citations
“…In this case, they suggested that aging and apoE4 expression cooperatively accelerated Ab aggregation in the brain through an increase in the level of GM1 in particular microdomains of neuronal membranes. These results suggest that Ab accumulation in these microdomains is an early event in the process of AD development (42).…”
Section: App Processing and Lipid Raftsmentioning
confidence: 63%
“…In this case, the level of sphingomyelin decreased significantly, but not the level of gangliosides. Yamamoto et al (42) reported that the concentration of GM1 in DRMs of synaptosomes increased with age and that this increase was more pronounced in brains of knock-in mice homozygous for the human apoE e4 allele, compared with those harboring two e3 alleles. In this case, they suggested that aging and apoE4 expression cooperatively accelerated Ab aggregation in the brain through an increase in the level of GM1 in particular microdomains of neuronal membranes.…”
Section: App Processing and Lipid Raftsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dutch-type, Italian-type, and Flemish-type A␤s), preferably assembles in the presence of GM1 ganglioside, as does wild-type A␤ (35,36). We also reported that GM1 ganglioside level increases in synaptosomes prepared from aged, human apolipoprotein E4 knock-in mice (37). Thus, it is possible that an alteration in the expression or distribution of GM1 ganglioside is the background to the assembly and deposition of A␤ in the brain parenchyma.…”
mentioning
confidence: 67%